2016
DOI: 10.1021/acs.inorgchem.6b01448
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Aryl Halides by Nickel(I) Pincer Complexes: Reaction Pathways of Stoichiometric and Catalytic Dehalogenations

Abstract: Homolytic C-X bond cleavage of organohalides by the T-shaped nickel(I) complexes [LigNi(I)] 1 bearing the iso-PyrrMeBox ligand had been found previously to be the crucial activation step in the asymmetric hydrodehalogenation of geminal dihalides. Here, this mechanistic investigation is extended to aryl halides, which allowed a systematic study of the activation process by a combination of experimental data and density functional theory modeling. While the activation of both aryl chlorides and geminal dichlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 82 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…On the basis of the above experimental observations and previous reports, [4j, 6a, e, 17] ap roposed mechanism for the arylation is shown in Scheme6.Most likely, catalyst 1 is transformed into the active complex A,which reacts with 2a throughaturnover-limiting CÀHn ickelation to deliver the nickelacycle B.A lternatively, 1 would react directly with 2a in the presence of LiHMDS to generate intermediate B.S pecies B would trigger the radicalg eneration through iodine atom transfer (IAT) to form C,f ollowed by the radical rebound to give the Ni IV species D.R eductive elimination will then give the product 4aa and regenerate the catalyst 1.A lternately, B would activate 4iodotoluenei nabimolecular oxidative fashion to deliver [Ni III ] (E)a nd Ni III I( C). [18] Reductive elimination of 4aa from E would produce Ni I species F,w hich upon disproportionation with C regenerates 1 and B to complete the cycle. [19] Scheme3.Nickel-catalyzed CÀHa rylation of indoles.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…On the basis of the above experimental observations and previous reports, [4j, 6a, e, 17] ap roposed mechanism for the arylation is shown in Scheme6.Most likely, catalyst 1 is transformed into the active complex A,which reacts with 2a throughaturnover-limiting CÀHn ickelation to deliver the nickelacycle B.A lternatively, 1 would react directly with 2a in the presence of LiHMDS to generate intermediate B.S pecies B would trigger the radicalg eneration through iodine atom transfer (IAT) to form C,f ollowed by the radical rebound to give the Ni IV species D.R eductive elimination will then give the product 4aa and regenerate the catalyst 1.A lternately, B would activate 4iodotoluenei nabimolecular oxidative fashion to deliver [Ni III ] (E)a nd Ni III I( C). [18] Reductive elimination of 4aa from E would produce Ni I species F,w hich upon disproportionation with C regenerates 1 and B to complete the cycle. [19] Scheme3.Nickel-catalyzed CÀHa rylation of indoles.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…2. Because the C–N bond activation and decarbonylative process have been confirmed in our previous work3031, we suspected that the formed intermediate C′ in aliphatic amides could occur homolytic cleavage reversibly49. Nonetheless, details for the mechanism of this reaction are not clear at present and more studies are required to fully elucidate the reaction mechanism.…”
Section: Discussionmentioning
confidence: 73%
“…[1][2][3][4][5] Among the numerous HDH methods that have been developed, [6][7][8][9][10][11][12][13][14][15] nickel pincer complexes have recently emerged as attractive, stable, homogeneous catalysts for such reactions. [16][17][18][19][20][21] In 2012, the Hu group reported that "Nickamine" [16,22] (complex A in Figure 1) could be used as a precatalyst for hydrodehalogenation reactions of both aryl and alkyl halides by employing diethyloxymethylsilane as reductant and sodium methoxide as base. Rettenmeier, Wadepohl and Gade found that a chiral Ni(NNN) complex, B, (Figure 1) can be transformed to a stable Ni(I) derivative via reaction with LiBEt 3 H and could be used to effect stereoselective HDH of various alkyl halides via a radical mechanism.…”
Section: Introductionmentioning
confidence: 99%